2022
DOI: 10.3390/nu14102006
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Home-Delivery Produce Prescription Program to Address Food Insecurity and Diet Quality in Adults and Children

Abstract: Produce prescription programs aim to improve food insecurity (FI) and nutrition but their effectiveness is unclear. We conducted a pilot study to demonstrate the feasibility and explore the potential impact of a family-based, home-delivery produce prescription and nutrition education program. We measured enrollment, satisfaction, participation, and retention as measure of feasibility. Adult participants answered pre-post self-report questionnaires assessing FI, child and adult fruit and vegetable intake, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 49 publications
2
45
1
Order By: Relevance
“…Participants found the online market unappealing, citing the smaller variety of produce available online and the inability to hand pick the produce as reasons for not favoring this option. Contrary to our findings, previous research has found that delivery services enhanced participation in Produce Rx programs among low-income households in urban settings [ 22 ]. In the future, program improvements could be made to overcome other barriers cited by participants.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Participants found the online market unappealing, citing the smaller variety of produce available online and the inability to hand pick the produce as reasons for not favoring this option. Contrary to our findings, previous research has found that delivery services enhanced participation in Produce Rx programs among low-income households in urban settings [ 22 ]. In the future, program improvements could be made to overcome other barriers cited by participants.…”
Section: Discussioncontrasting
confidence: 99%
“…Participants were particularly motivated by the positive effect that the program had both on the child and shared that the benefits were experienced by other family members, even though the program was really designed for just the participating child. This was similar to another pilot study which found that enhanced family bonding and positive experiences for children as a benefit of a Produce Rx program [ 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, there is very limited data available on food delivery produce prescription programs in urban pediatric populations. [12][13][14][15] As pediatric practices continue to expand produce prescription models as a viable FI intervention, it is important to understand the lived experiences of clinicians to ensure these intervention strategies are feasible within their busy workflow. In addition, while there are studies that detail caregivers' perspective on food resources and food prescription programs, there are limited data regarding the experiences of pediatric clinicians referring patients into these programs and how they perceive these programs' effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, while there are studies that detail caregivers' perspective on food resources and food prescription programs, there are limited data regarding the experiences of pediatric clinicians referring patients into these programs and how they perceive these programs' effectiveness. [11][12][13][14][15][16] To address these gaps in research, pediatric clinicians were interviewed to explore their experiences after enrolling patients in a novel produce prescription program in an urban primary-care clinic in Washington, DC.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of produce prescription programs have found that, in addition to limited proximity to prescription redemption locations, barriers to redeeming produce prescriptions include limited mobility, limited or unreliable transportation, and lack of childcare . In recent years, produce prescription programs have begun to deliver fruits and vegetables to participants’ homes, but these have been pilot studies or serve adults …”
mentioning
confidence: 99%